Dietary Fiber Consumption and Colorectal Cancer: A Case-Control Study - Rahman, Irtika; Islam, Md Ziaul (Journal of Preventive and Social Medicine, 2023)
Background: Colorectal cancer (CRC) is an increasingly imperative cause of morbidity and mortality. This study aimed to determine the association between dietary fiber consumption and CRC. Methods: This age- and sex-matched case-control study was conducted from July 2020 to June 2021 at the Combined Military Hospital (CMH) and the National Institute of Cancer Research and Hospital (NICRH) in Dhaka. A total of 102 cases and 102 controls were selected through purposive sampling. Cases were adult patients diagnosed with CRC, while controls were individuals without cancer. Data were collected using a pretested semistructured questionnaire and checklist, which included information on socio-demographic characteristics, colorectal cancer attributes, and dietary fiber consumption. Face-to-face interviews were conducted to collect data from both cases and controls. Results: The mean (±SD) age of the cases and controls were 44.7±13.9 years and 45.6±13.3 years, respectively, with a male-female ratio of 1:1.3 in both groups. A significantly higher proportion of cases (53.9%) lived in joint families compared to controls (39.2%) (p=0.035). Type 2 diabetes mellitus (T2DM) was significantly more prevalent in cases (27.5%) than in controls (15.7%) (p=0.041) among the comorbid conditions. Majority of the cases (72.5%) consumed low dietary fiber (<25 grams/day), while three-fifths of the controls (67.6%) consumed normal to high dietary fiber daily (p<0.001). After adjusting for the type of family, residence, and presence of T2DM, participants who consumed low dietary fiber were found to be 7 times more likely to develop CRC than those who consumed normal or high dietary fiber (OR=7.003, 95% CI = 3.616-13.565, p<0.001) based on binary logistic regression. Conclusion: The findings of this study suggest that low dietary fiber consumption is associated with an increased risk of CRC. Specific measures that could be taken to promote a high-fiber diet include increasing awareness through public health campaigns, providing nutrition education, and ensuring that healthy food options are readily available and accessible to people from all socioeconomic backgrounds. JOPSOM 2021; 41(1):1-7